The Lists of Necropolis Workmen in Theban Graffiti and Ostraca of the 21st Dynasty.: Consequence on the Chronology of this Period - Antoine, Jean-Christophe (Zeitschrift für ägyptische Sprache und Altertumskunde, 2019)
Lists of workmen of the 21 st dynasty mentioned on ostraca of the Valley of the Kings and graffiti of the Theban Necropolis have not been fully studied. We analyzed 113 workmen, scribes and foremen of the Tomb named in these documents. A comparison of the composition of the crew between lists of the 21st dynasty and lists of the reign of Ramesses XI allowed their chronological ordering. A model of the progressive renewal of individuals with time in securely dated lists of the Ramesside Period was built to date the 21st dynasty lists. Results suggest that Renaissance lasted about 12 years, was followed by a period of about 11 years and then by another one associated with Pinedjem I. These results support the chronology and dating system proposed by K. Jansen-Winkeln with dates referring to the pontificate/reign of Herihor, Pinedjem I and Menkheperre. Consequences on the composition of the gang of workmen, their activity and individual chronology and prosopography are analyzed.